Progranulin Adsorbs to Polypropylene Tubes and Disrupts Functional Assays: Implications for Research, Biomarker Studies, and Therapeutics - Gururaj, Sushmitha; Sampognaro, Paul J.; Argouarch, Andrea R.; Kao, Aimee W. (Frontiers in Neuroscience, 2020)
Progranulin (PGRN) is a tightly regulated, secreted glycoprotein involved in a wide range of biological processes that is of tremendous interest to the scientific community due to its involvement in neoplastic, neurodevelopmental, and neurodegenerative diseases. In particular, progranulin haploinsufficiency leads to frontotemporal dementia. While performing experiments with a HIS-tagged recombinant human (rh) PGRN protein, we observed a measurable depletion of protein from solution due to its adsorption onto polypropylene (PPE) microcentrifuge tubes. In this study, we have quantified the extent of rhPGRN adsorption to PPE tubes while varying experimental conditions, including incubation time and temperature. We found that ~25-35% of rhPGRN becomes adsorbed to the surface of PPE tubes even after a short incubation period. We then directly showed the deleterious impact of PGRN adsorption in functional assays and have recommended alternative labware to minimize these effects. Although the risk of adsorption of some purified proteins and peptides to polymer plastics has been characterized previously, this is the first report of rhPGRN adsorption. Moreover, since PGRN is currently being studied and utilized in both basic science laboratories to perform in vitro studies and translational laboratories to survey PGRN as a quantitative dementia biomarker and potential replacement therapy, the reported observations here are broadly impactful and will likely significantly affect the design and interpretation of future experiments centered on progranulin biology.